Comparison of Stool Antigen Test and CLO Test in Diagnosis of Helicobacter pylori Infection (Jalalabad Medical Journal, 2025)
Helicobacter pylori (H. pylori) is a major cause of gastrointestinal diseases. Effective antimicrobial treatment depends on accurate diagnostic approaches. Stool antigen tests have recently been welcomed with great expectations as they are convenient for patients and can be easily performed even in small laboratories. The objective of the study was to explore the diagnostic usefulness of stool antigen test for H. pylori infection in dyspeptic patients. This cross-sectional study was conducted in the Department of Microbiology, Sylhet MAG Osmani Medical College, Sylhet, from July 2012 to June 2013. A total of 150 dyspeptic patients were enrolled. Exclusion criteria were chronic liver disease, carcinoma stomach, coagulopathy, treatment with antibiotics within the last 4 weeks, and taking NSAIDs. Upper GI endoscopy was performed using a video endoscope, and biopsy materials were taken from the antrum and body of the stomach and tested for presence of H. pylori infection by a rapid urease test (CLO test). Stool was collected for detection of H. pylori antigen by an immunochromatographic tests (ICT) kit. The mean age of the patients were 43.35±16.30 years, and male to female ratio was 1.63:1. CLO and stool antigen tests were positive in 64.7% and 48.7% of patients, respectively. The sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of the stool antigen test in the diagnosis of H. pylori infection was 72.7%, 94.3%, 95.9%, 64.9% and 80%, respectively. CLO test (Invasive) is still superior to the stool antigen (Non-invasive) in the diagnosis of H. pylori infection in dyspeptic patients. Jalalabad Med J 2024; 21 (1): 6-10